Fostering Higher-Order Thinking Skills in Mathematics Education: Strategies, Challenges, and Classroom Practices - Gradini, Ega; Firmansyah B, Firmansyah B; Noviani, Julia; Ulya, Khairatul (Universitas Pendidikan Mandalika, 2025)
Despite increasing emphasis on Higher-Order Thinking Skills (HOTS) in mathematics curricula, classroom implementation remains limited and inconsistent. This qualitative study explored HOTS implementation in mathematics education, aimed to (1) identify effective instructional strategies for fostering HOTS, (2) examine teacher’ challenges, and (3) analyze classroom practices. The study involved 25 stratified junior high school mathematics teachers, with data collected over one academic year through semi-structured interviews, classroom observations, and document analysis. Thematic analysis followed Braun and Clarke’s six-phase framework.. The study highlights that an integrated instructional framework combining inquiry-based learning, collaborative practices, progressive learning support tailored to student needs, and technology significantly enhances higher-order thinking in mathematics. It demonstrates that aligning teacher beliefs, professional development, and systemic curricular support not only validates but also strengthens effective pedagogy for meeting the contemporary demands of critical thinking and problem-solving. Implementation is hindered by misalignment between curriculum goals and classroom realities, assessment practices, and theoretical professional development. Mathematics classrooms are progressively shifting toward critical problem-solving approaches, with teachers integrating analysis, evaluation, and creative tasks. Students demonstrate greater engagement with authentic tasks that connect to real-world contexts. These findings support the redesign of professional development programs and curriculum planning to enhance HOTS implementation in mathematics education.